Current Evidence of Measurement Properties of Physical Activity Questionnaires for Older Adults: An Updated Systematic Review - Sattler, Matteo C. (Sports Med, 2020)
BACKGROUND: Questionnaires provide valuable information about physical activity (PA) behaviors in older adults. Until now, no firm recommendations for the most qualified questionnaires for older adults have been provided. OBJECTIVES: This review is an update of a previous systematic review, published in 2010, and aims to summarize, appraise and compare the measurement properties of all available self-administered questionnaires assessing PA in older adults. METHODS: We included the articles evaluated in the previous review and conducted a new search in PubMed, Embase, and SPORTDiscus from September 2008 to December 2019, using the following inclusion criteria (1) the purpose of the study was to evaluate at least one measurement property (reliability, measurement error, hypothesis testing for construct validity, responsiveness) of a self-administered questionnaire; (2) the questionnaire intended to measure PA; (3) the questionnaire covered at least one domain of PA; (4) the study was performed in the general, healthy population of older adults; (5) the mean age of the study population was > 55 years; and (6) the article was published in English. Based on the Quality Assessment of Physical Activity Questionnaires (QAPAQ) checklist, we evaluated the quality and results of the studies. The content validity of all included questionnaires was also evaluated using the reviewers’ rating. The quality of the body of evidence was evaluated for the overall construct of each questionnaire (e.g., total PA), moderate-to-vigorous physical activity (MVPA) and walking using a modified Grading of Recommendation, Assessment, Development, and Evaluation (GRADE) approach. RESULTS: In total, 56 articles on 40 different questionnaires (14 from the previous review and 26 from the update) were included. Reliability was assessed for 22, measurement error for four and hypotheses testing for construct validity for 38 different questionnaires. Evidence for responsiveness was available for one questionnaire. For many questionnaires, only one measurement property was assessed in only a single study. Sufficient content validity was considered for 22 questionnaires. All questionnaires displayed large measurement errors. Only versions of two questionnaires showed both sufficient reliability and hypotheses testing for construct validity, namely the Physical Activity Scale for the Elderly (PASE; English version, Turkish version) for the assessment of total PA, and the Physical Activity and Sedentary Behavior Questionnaire (PASB-Q; English version) for the assessment of MVPA. The quality of evidence for these results ranged from very low to high. CONCLUSIONS: Until more high-quality evidence is available, we recommend the PASE for measuring total PA and the PASB-Q for measuring MVPA in older adults. However, they are not equally qualified among different languages. Future studies on the most promising questionnaires should cover all relevant measurement properties. We recommend using and improving existing PA questionnaires—instead of developing new ones—and considering the strengths and weaknesses of each PA measurement instrument for a particular purpose. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40279-020-01268-x) contains supplementary material, which is available to authorized users.